Design and Implementation of an Android-Based Scholarship Search Application Using Web Scraping Techniques - Diah Arifah Prastiningtyas; M. Noval Hidayat (LPPM STIKI MALANG, 2025)
Education is a vital need for humans; however, high education costs often become a barrier for students, particularly those from underprivileged backgrounds. Although scholarships offer an alternative solution, scholarship information is commonly scattered across multiple platforms and difficult to access efficiently. This study aims to design and implement an Android-based scholarship search application using web scraping techniques to integrate and centralize scholarship information from various reliable sources. The main contribution of this research lies in the application of automated web scraping using Google Cloud Function to support a mobile-based scholarship information system, enabling periodic data collection and real-time access to updated scholarship data. The scraping process runs every 24 hours and stores structured data in a Firestore database, which is then presented through an Android application developed using Kotlin and Jetpack Compose. Analytical results from usability testing indicate that 90% of users rated the application as easy or very easy to use, while system performance evaluation shows that all core features functioned successfully with fast data retrieval and display. Black-box testing confirms that searching, filtering, sorting, and favorite management features operate as expected. This application provides an effective solution for students to efficiently search and manage scholarship information through an integrated platform. Future development may focus on improving scraping performance, enhancing the user interface, and adding notification features for newly available scholarships